Synergistic interaction between ABA and IAA due to moderate soil drying promotes grain filling of inferior spikelets in rice. (29th December 2021) - Teng, Zhenning; Yu, Huihui; Wang, Guanqun; Meng, Shuan; Liu, Bohan; Yi, Yake; Chen, Yinke; Zheng, Qin; Liu, Ling; Yang, Jianchang; Duan, Meijuan; Zhang, Jianhua; et al.
SUMMARY: Poor grain filling of inferior spikelets is becoming a severe problem in some super rice varieties with large panicles. Moderate soil drying (MD) after pollination has been proven to be a practical strategy to promote grain filling. However, the molecular mechanisms underlying this phenomenon remain largely unexplored. Here, transcriptomic analysis of the most active grain filling stage revealed that both starch metabolism and phytohormone signaling were significantly promoted by MD treatment, accompanied by increased enzyme activities of starch synthesis and elevated abscisic acid (ABA) and indole‐3‐acetic acid (IAA) content in the inferior spikelet. Moreover, the IAA biosynthesis genes OsYUC11 and OsTAR2 were upregulated, while OsIAA29 and OsIAA24, which encode two repressors of auxin signaling, were downregulated by MD, implying a regulation of both IAA biosynthesis and auxin signal transduction in the inferior spikelet by MD. A notable improvement in grain filling of the inferior spikelet was found in the aba8ox2 mutant, which is mutated in an ABA catabolism gene. In contrast, overexpression of OsABA8ox2 significantly reduced grain filling. Interestingly, not only the IAA content, but also the expression of IAA biosynthesis and auxin‐responsive genes displayed a similar trend to that in the inferior spikelet under MD. In addition, several OsTPP genes were downregulated in the inferior spikelets of both MD/ABA‐treated wild‐type plants and the aba8ox2 mutant, resulting in lower trehalose content and higher levels of ‐6‐phosphate (T6P), thereby increasing the expression of OsTAR2, a target of T6P. Taken together, our results suggest that the synergistic interaction of ABA‐mediated accumulation of IAA promotes grain filling of inferior spikelets under MD. Significance Statement: Post‐anthesis moderate soil drying can increase ABA content in inferior spikelets, which will then activate IAA biosynthesis and IAA signaling. Together, both elevated ABA and IAA play a key role in promoting grain filling of inferior spikelets.